Higher Incidence of B Cell Malignancies in Primary Immunodeficiencies: A Combination of Intrinsic Genomic Instability and Exocytosis Defects at the Immunological Synapse - Mastio, Jérôme; Saeed, Mezida B.; Wurzer, Hannah; Krecke, Max; Westerberg, Lisa S.; Thomas, Clément (Frontiers in Immunology, 2020)
Congenital defects of the immune system called primary immune deficiency disorders (PIDD) describe a group of diseases characterized by a decrease, an absence, or a malfunction of at least one part of the immune system. As a result, PIDD patients are more prone to develop life-threatening complications, including cancer. PIDDs currently include over 400 different disorders, however, the variety of PIDD-related cancers is narrow. We discuss here reasons for this clinical phenotype. Namely, PIDDs can lead to cell intrinsic failure to control cell transformation, failure to activate tumor surveillance by cytotoxic cells or both. As the most frequent tumors seen among PIDD patients stem from faulty lymphocyte development leading to leukemia and lymphoma, we focus on the extensive genomic alterations needed to create the vast diversity of B and T lymphocytes with potential to recognize any pathogen and why defects in these processes lead to malignancies in the immunodeficient environment of PIDD patients. In the second part of the review, we discuss PIDD affecting tumor surveillance and especially membrane trafficking defects caused by altered exocytosis and regulation of the actin cytoskeleton. As an impairment of these membrane trafficking pathways often results in dysfunctional effector immune cells, tumor cell immune evasion is elevated in PIDDs. Considering new anti-cancer treatment concepts include genetically engineered immune cells, restoration of anti-tumor immunity in PIDD patients could be an approach that complements standard treatment options.